KUAT TEKAN BETON MENGGUNAKAN BAHAN CAMPURAN PASIR LOKAL (PASIR NASEM) DAN PASIR IMPOR DENGAN METODE DoE - Abner Doloksaribu; Muchlis Alahudin (Universitas Musamus, Merauke, Papua, 2016)
Concrete is element authors and used the structure of the building, if concrete of good quality shall be hold burden building a great structures can exists when supported by structure a good structure good can create security and comfort for occupant who occupy the building, concrete used for construction, for example: building roads, bridges, airport, reservoir, the pier the dam and etc. The sands contained in kabupaten Merauke are generally unable to meet the power desired when used as of ingredients mixed concrete structure except use sand import.This research use of ingredients mixed concrete use sand from Nasem to be interfering with sand import, aggregate rough, a fastener Portland cement material type I and by the firm production introductory water drinking water areas that could receive strong press uses the DoE (the department of environment).Researched process it uses design mix with the experimental methods and testing. Objects test made from comparison namely by some the proportion of comparison mixture.